Ethical Considerations for Wildlife Reintroductions and Rewilding - Thulin, Carl-Gustaf; Röcklinsberg, Helena (Frontiers in Veterinary Science, 2020)
The recovery of many populations of large carnivores and herbivores in major parts of Europe and North America offers ecosystem services and opportunities for sustainable utilization of wildlife. Examples of services are hunting, meat, and skin, along with less invasive utilization such as ecotourism and wildlife spotting. An increasing number of studies also point out the ecosystem function, landscape engineering, and cascading effects of wildlife as values for human existence, biodiversity conservation, and ecosystem resilience. Within this framework, the concept of rewilding has emerged as a means to add to the wilderness through either supplementary release of wildlife species already present or reintroduction of species formerly present in a certain area. The latter involves translocation of species from other geographical areas, releases from captivity, feralization, retro-breeding, or de-domestication of breeds for which the wild ancestor is extinct. While all these initiatives aim to reverse some of the negative human impacts on life on earth, some pose challenges such as conflicts of interest between humans and wildlife in, for example, forestry, agriculture, traffic, or disease dynamics (e.g. zoonosis). There are also welfare aspects when managing wildlife populations with the purpose to serve humans or act as tools in landscape engineering. These welfare aspects are particularly apparent when it comes to releases of animals handled by humans, either from captivity or translocated from other geographical areas. An ethical values clash is that translocation can involve suffering of the actual individual, while also contributing to reintroduction of species and reestablishment of ecological functions. This paper describes wildlife recovery in Europe and North America and elaborates on ethical considerations raised by the use of wildlife for different purposes, in order to find ways forward that are acceptable to both the animals and humans involved. The reintroduction ethics aspects raised are finally formulated in ten guidelines suggested for management efforts aimed at translocating wildlife or reestablishing wilderness areas.